Gypsy - Laurents, Arthur 1917-2011; Lee, Gypsy Rose 1911-1970; Styne, Jule 1905-1994; Sondheim, Stephen 1930-2021 (Warner Bros. Entertainment Inc., 2015)
"[...] Adaption des Broadway-Musicals "Gypsy", das den Aufstieg der in den 20er Jahren schließlich hochdotierten Stripperin Rose Lee behandelt. [...]" [filmdienst.de]
Orig.: USA, 1962
Special features: the pied of Guadalupe; theatrical trailer; deleted scenes; together wherever we go; you'll never get away from me
Bildformat 2.40:1
Keywords: Biographical films; Musical films; Film adaptations; Biografischer Film; Verfilmung; Musikfilm; Film; DVD-Video